2023
DOI: 10.1099/jmm.0.001733
|View full text |Cite
|
Sign up to set email alerts
|

Serological status for TORCH in women of childbearing age: a decade-long surveillance (2012–2022) in Italy

Abstract: Introduction. Serological screening and seroprevalence data for TORCH infections represent a key instrument to estimate immunity and vaccination levels and exposure rates to prevent and treat TORCH congenital infections. Hypothesis. Serology allows us to identify women susceptible to primary infection. Aim. Assess the prevalence of women at risk of primary infections by TORCH pathogens in Palermo, Sicily, Italy, in the decade 2012–2022. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Comparing the overall T. gondii seropositivity, the detected seroprevalence rate in Croatia (20.2%) was similar to the seroprevalence in Italy (20.9%, Palermo, 2012–2022) [ 18 ], Spain (21%, Albacete, 2006) [ 19 ], Poland (22.3%, 2018–2019) [ 20 ] and northern Kosovo and Metohija (24.1%, 2011–2012) [ 21 ]. Lower seropositivity was found in Serbia (12.7%, Belgrade, 2018–2019) [ 22 ], the United Kingdom (9.1%, Kent, 1999–2001; 17.32%, London, 2006–2008) [ 23 , 24 ] and in Turkey (14%, Karabük, 2008) [ 25 ], while higher seropositivity was found in France (31.3%, 2016) [ 26 ], Germany (39.5%, 2006–2018) [ 20 ], and the Netherlands (40.5%, 1995–1996) [ 27 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Comparing the overall T. gondii seropositivity, the detected seroprevalence rate in Croatia (20.2%) was similar to the seroprevalence in Italy (20.9%, Palermo, 2012–2022) [ 18 ], Spain (21%, Albacete, 2006) [ 19 ], Poland (22.3%, 2018–2019) [ 20 ] and northern Kosovo and Metohija (24.1%, 2011–2012) [ 21 ]. Lower seropositivity was found in Serbia (12.7%, Belgrade, 2018–2019) [ 22 ], the United Kingdom (9.1%, Kent, 1999–2001; 17.32%, London, 2006–2008) [ 23 , 24 ] and in Turkey (14%, Karabük, 2008) [ 25 ], while higher seropositivity was found in France (31.3%, 2016) [ 26 ], Germany (39.5%, 2006–2018) [ 20 ], and the Netherlands (40.5%, 1995–1996) [ 27 ].…”
Section: Discussionmentioning
confidence: 66%
“…In the United Kingdom, seroprevalence in Liverpool was lower (93.7%) than average for the northwestern region (96.3%) [ 47 ]. Italian studies showed lower seropositivity rates of 85.8% in Messina (2006–2007) [ 48 ], 88.6% in Tuscany and 84.3% in Apulia (2014–2016) [ 49 ] and 81.2% in Palermo (2012–2022) [ 18 ]. Similar seroprevalence of 83.5% was also found in Portugal [ 50 ].…”
Section: Discussionmentioning
confidence: 99%